Managing customers relationships in Slovenian companies - Iča Rojšek (Journal for East European Management Studies, 2001)
In the past two decades, the relationship between suppliers and customers has undergone a considerable changing process all over the world: both parties place a greater emphasis on the search for synergies in mutual relationships, sincere conversation and trust nurturing. The tendency to cut the number of suppliers is also evident. All stated and also other factors have inevitably led to major changes in the area of business-to-business marketing. We intent to point out some of these changes and also to examine responses of the Slovenian manufacturing businesses studied to the changes. The analytical part of the paper is based on a research project that has been carried out on the sample of fifty Slovenian manufacturing companies by the Faculty of Economics in Ljubljana for the past three years. – – Während der vergangenen beiden Jahrzehnte hat das Verhältnis von Lieferanten und Kunden auf der ganzen Welt einen nachhaltigen Veränderungsprozess durchlaufen: auf beiden Seiten wird ein höherer Wert auf Synergien im gegenseitigen Verhältnis gelegt. Dabei spielen Ehrlichkeit und Vertrauen eine wichtige Rolle. Außerdem wird eine Tendenz zur Beschränkung der Anzahl der Lieferanten deutlich. Die genannten und andere Faktoren haben zu tiefgreifenden Veränderungen auf dem Gebiet des Business-to-Business Marketing geführt. Im vorliegenden Artikel werden einige dieser Veränderungen aufgezeigt. Außerdem werden die Reaktionen einiger slowenischer Produktionsbetriebe ausgewertet. Der analytische Teil der Arbeit basiert auf einem Forschungsprojekt mit fünfzig slowenischen Betrieben, das von der Fakultät für Wirtschaft in Ljubljana über die vergangenen drei Jahre durchgeführt wurde.
Keywords: 650